2016
DOI: 10.7567/jjap.55.07le02
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hydrogenated diamond-like carbon films using high-density pulsed plasmas of Ar/C2H2 and Ne/C2H2 mixture

Abstract: Hydrogenated diamond-like carbon films are prepared using reactive high-density pulsed plasmas of Ar/C 2 H 2 and Ne/C 2 H 2 mixture in the total pressure range from 0.5 to 2 Pa. The plasmas are produced using a reactive high-power impulse magnetron sputtering (HiPIMS) system. A negative pulse voltage of %500 V is applied to the substrate for a period of 15 µs in the afterglow mode. The growth rate does not strongly depend on the type of ambient gas but it markedly increases to about 2.7 µm/h at a C 2 H 2 fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The potential of HiPIMS has been explored for the production of DLC thin films by several authors and it has shown promising results. [13][14][15][16][17][18] However, conventional Ar-C HiPIMS discharges have been found to exhibit significantly smaller degree of ionization of sputtered material 14 as opposed to their Ar-metal counterparts 19,20 rendering HiPIMS insufficient for synthesizing high quality DLC films. We have recently addressed this challenge 21 by developing a novel Nebased HiPIMS process; the presence of Ne as a sputtering gas resulted in a substantial increase of the electron temperature as compared to Ar-based HiPIMS process.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of HiPIMS has been explored for the production of DLC thin films by several authors and it has shown promising results. [13][14][15][16][17][18] However, conventional Ar-C HiPIMS discharges have been found to exhibit significantly smaller degree of ionization of sputtered material 14 as opposed to their Ar-metal counterparts 19,20 rendering HiPIMS insufficient for synthesizing high quality DLC films. We have recently addressed this challenge 21 by developing a novel Nebased HiPIMS process; the presence of Ne as a sputtering gas resulted in a substantial increase of the electron temperature as compared to Ar-based HiPIMS process.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal was to obtain hard coatings with low friction coefficients and wear rates, and with smooth surface. Two main approaches were followed and combined for tuning the process: (i) addition of Ne into the gas mixture, in order to improve the C ionization [18,34] and (ii) use of acetylene to increase the deposition rate through the contribution of C atoms from decomposition of gas precursor [10,35].…”
Section: Process Descriptionmentioning
confidence: 99%
“…One of the main factors determining the sp 3 bonding in DLC is the ion bombardment, with an optimum energy around 100 eV for impinging C + ions [9]. For the hydrogenated coatings in particular, where some of the carbon-carbon bonding can be converted into carbon-hydrogen, the bombardment with a sufficient number of ions that have the appropriate kinetic energy becomes even more important in increasing the fraction of sp 3 bonds [10]. For the case of magnetron sputtering, significant ionization of sputtered atoms can be usually achieved by applying high power pulses, technique known as high power impulse magnetron sputtering (HiPIMS) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study with rather high frequency (250 Hz to 1 kHz), the plasma was found to have larger ionized species yielding enhance densification with larger sp 3 fraction [9]. In more recent, works Ar and C 2 H 2 gas mixture were used to deposit a-C films but films were not H free [13,14]. Clearly, HiPIMS offers possibilities to deposit carbon thin films with high density and high sp 3 fractions, and more systematic studies are required to achieve this.…”
Section: Introductionmentioning
confidence: 98%